New method for determining the optical rotatory dispersion of hydroxypropyl cellulose polymer solutions in water. Issue 5 (30th June 2014) - Barzic, Andreea Irina; Dimitriu, Dan Gheorghe; Dorohoi, Dana Ortansa
<x xml:space="preserve">Abstract</x> The proposed method employs the recorded channeled spectrum of an optical active medium (crystal or liquid solution) placed between two crossed polarizers. The method of channeled spectrum, previously validated for quartz samples, is used to determine the optical rotatory dispersion of hydroxypropyl cellulose solutions (HPC) in water. Both the specific rotation and dispersion parameter depend on the wavelengths of the maxima and minima from the channeled spectrum and on the thickness of the optical active sample. The circular birefringence and its dispersion determined for HPC solutions in water of concentrations 30% and 45% were estimated with a precision of about 0.5%. The rotatory birefringence of HPC in water at 45% is (119.75–57.60)10−6 and the specific rotation determined in the visible range for these solutions has values between 4782 and 1402 degrees/dm, in agreement with the literature. The specific rotation (angle) of HPC solutions is independent of the polymer concentration and represents a dispersive parameter which decreases with the light wavelength. POLYM. ENG. SCI., 55:1077–1081, 2015. © 2014 Society of Plastics Engineers